Study Of Survival Strategies Of Hong Kong SMEs Under The Current Global Situation - Mong Kwan Jacky Watt (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
Due to intense market competition and economic globalization, many small and medium-sized enterprises (SMEs) in Hong Kong face uncertain challenges, leading to a relatively high failure rate in the short term after opening. To cope with these challenges, SMEs must adopt survival strategies. This study examines SMEs' global challenges and how they can enhance their competitiveness. The review identifies five significant challenges: new market development, restructuring through operational integration, cost reduction, improved research and development, and transfer to other markets. The study also considers the survival strategies of SMEs and the external and internal factors that influence business sustainability. A theoretical examination of SMEs' survival strategies based on data collected in October 2023 from 317 SMEs is included in this study.